INFORMATIONAL APPROACH ON TRAINING PROCESS - Šemsudin Plojović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Information technology is very important part in training process. Training process is always in innovation and assembling faze, especially at those that want to compete on international level. In that surrounding training process, as the trainers also, must be transformed. Great deal of information must be reliable for headquarter for optimal training process. Informational approach on training process, subject of this research, represent informational technologies and information systems with all aspects an possibilities of applications in sport. Information technology, information system and its application in sport in last decade is developed very fast in last decade. Computer is used, not only for data process, but also for making decisions. That is the key moment changing the basics of information system, especially the role of information system in training process. To define key words connected for information systems in sport we will start from characteristics of information, exchanging in this relations: man to man, machine to machine, man to machine, and opposite, machine to man. According to this we need to make the difference between data and information. In this research we talk about concrete application of information technology and information system as the backup of training process. Behind practical application of IT in sport, that is the main issue of this work, stands the marvelous results of athletes from AK Novi Pazar. Azra Eminovic, Edin Zukovic, Muamer Hasanovic, Emir Koca and Senadin Plojovic, they've achieved great results with information back up of training process.